Histomorphological Evaluation of Vitamin E’s Protective Role Against Bisphenol A-Induced Testicular Toxicity in Wistar Rats - Sadia Saqib, Nadia Haq, Raafea Tafweez, Ahmed Fawad Syami, Irfan Ali, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Bisphenol A (BPA) exposure has been broadly implicated in male reproductive dysfunction,primarily via oxidative damage to testicular tissues. This experimental study aimed to evaluatetesticular histomorphological alterations induced